Menstruation and the Bar Exam: Unconstitutional Tampon Bans - Crawford, Bridget J. (Columbia Journal of Gender and Law, 2021)
Some states have policies that prevent bar exam candidates from bringing their own menstrual products to the test. Via social media, awareness of these policies achieved new heights in the weeks leading up to the July 2020 bar exam. A small number of jurisdictions responded to public criticism by permitting test takers to bring menstrual products with them to the exam, whether administered traditionally or remotely in response to the COVID-19 pandemic. Not all states have adopted permissive policies, however. This Essay explains why outright bans on menstrual products at the bar exam likely are unconstitutional. So-called alternate policies, such as making menstrual products available in women’s restrooms, are inadequate. Only a “free-carry” policy for menstrual products is consistent with welcoming all qualified candidates to the legal profession, without regard to biology.